Critical Review on the Implementation of Transit Oriented Development in Malaysia by Comparison with Other Countries - Rahaman Lutfi A.; Naharudin Nabilah; Salleh Siti Aekbal (E3S Web of Conferences)
This paper review assesses the implementation of Transit Oriented Development (TOD) in Malaysia by comparing it with practices in other countries. The study aims to evaluate the principles of TOD and identify similarities and differences across different regions. Using a systematic literature analysis approach, the methodology involves examining manuals, journals, and government documents related to TOD policies. By employing VOSviewer software for network analysis of scientific publications, the research explores the structure of TOD principles. Key findings emphasize the importance of mixed-use development, high density, connectivity, liveability, resilience, green and low carbon principles, and resource optimization in fostering sustainable communities because some transit station in Malaysia can be improve its current infrastructure to meet TOD principles requirement. The conclusions drawn underscore the global significance of TOD practices and suggest avenues for Malaysia to enhance its urban planning policies by learning from international experiences. This study hopes to contribute valuable insights to the field of sustainable urban planning and offers implications for future research and policy development in TOD implementation.